Recycling of the MSW in the Slovak Republic - Dubravská, Mariana (Journal of Economic Development, Environment and People, 2014)
The Paper aims at recycling of the MSW in the condition of Slovak Republic. Waste management is facing big criticism in Slovakia. It is one of the environmental policies that is written in political strategies but not taken seriously. Environmental policy has not been given any priority in the government for many years. The changes came together with EU membership. Standard scientific research methods included synthesis, analysis and comparative method